Pengaruh Kepemimpinan Efektif Kepala Ruangan terhadap Kinerja Perawat Pelaksana - Tri Diani Agustuti Agustuti; Tri Kurniati; Aziz Alimul Hidayat; Farida Murtiani (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2022)
Background of Study : Improving the quality of nurses in providing quality nursing care to clients requires a leadership role in influencing and moving the nurse. The purpose of this study is to see the effect of effective leadership of the head of the room on the performance of the implementing nurses in RSPI Prof. Dr. Sulianti Saroso. Methods : This study was descriptive analytic research with cross sectional design. The sample of this study were 131 nurses at RSPI Prof. Dr. Sulianti Saroso. The data were taken by using purposive sampling technique. Collecting data using a questionnaire. Univariate analysis using frequency distribution, bivariate analysis using chi square.Results : There was a relationship between effective leadership and performance (P value = 0.000). The analysis of the independent sub-variables on the performance of all variables stated that there was a relationship because of sig 0.05 including knowledge (0.000), self-awareness (0.002), self-awareness (0.009), communication (0.019), energy use (0.000), goal setting (0.012), taking action (0.000).Conclusion : The variables that have significant relationship with the nurse's performance are effective leadership. It is expected that the hospital will seek to make policy and planning of nursing resources through the provision of continuous education, training / skills related courses, and seminars related to leadership in nursingKeywords : Leadership, Performance, Effective Leadership, Direction Functions